Implementation of Academic Supervision of Junior High School Supervisors in Indonesia - Akmal Udin; Rohiat rohiat; Rambat Nur Sasongko; Ali man (PendIPA Journal of Science Education, 2020)
The aim of this study was to describe: (1) the planning of academic supervision (2) the implementation of academic supervision, and (3) the follow-up of academic supervision. The significance of the study was expected to improve the competence of teachers, supervisors, and headmaster to achieve qualified educational goals. The research method applied was qualitative descriptive method. The data of qualitative research were in the form of words analyzed by terminology of individual and group responses.  The data collection was done through the technique of (1) observation, (2) interview, and (3) documentation. The results of the study showed that: (1) the planning of academic supervision in Book 1 contained Graduate Competence Standard, Syllabus, Lesson Plan, and Minimal Completeness Criteria), Book 2 contained (teacher ethics code, teacher vow, teacher discipline, teacher habituation, academic calendar, time allocation, annual program, semester program, teacher's agenda journal), Book 3 contained (attendance list, grades list, personality assessment, daily test analysis, improvement and enrichment program, teacher and student handbook, teaching schedule, student absorption, collection of test specification, collection of tests, test item analysis, test item improvement) Book 4 contained (teacher work self-evaluation list and teacher work follow-up program) the majority of teachers had not been able to have them at the beginning of entering school, (2) the implementation of class supervision had not been able to be conducted well, (3) the follow-up of supervision was submission of supervision results in the form of comments for improvement, reinforcement, and suggestions. Based on the findings the study, the researchers concluded that the implementation of academic supervision of Junior High School supervisors needed to be improved. Teachers, headmaster, supervisors, must have strong partnership to improve the quality of education.